GENDER ISSUES DURING SIMULTANEOUS INTERPRETING IN VIOLENCE AGAINST WOMEN - Varela, Alicia López (POLISSEMA – Revista de Letras do ISCAP, 2019)
While there are a number of general operating standards in Simultaneous Interpreting (SI) that are known and accepted by most interpreters, no guidelines exist regarding the gender of the interpreter. The aim of this study, which includes an experiment, a questionnaire filled in by the interpreters and a survey answered by a highly representative audience, is to determine how and to what extent the interpreters' gender may influence a group of interpreters within the context of violence against women. In addition to gender, empathy is the second key theoretical concept used in this study. The results of this research suggest that, although there appear to be no fundamental differences in terms of the amount of information conveyed by a group of male interpreters as opposed to a group of female interpreters, and that empathy does not seem to play a fundamental role, there are some distinctive discursive factors particular to the speech of female and male interpreters which can readily be distinguished by an audience. Therefore, when working in such situations, exclusively using the services of female interpreters may be more appropriate.